Violations of Article 3 of the ECHR in the detention conditions of migrant minors - Biksone, Kristiāna Jana (Riga Graduate School of Law, 2023)
The safeguards provided by Article 3 of the European Convention on Human Rights reinforce the Council of Europe's commitment to uphold human dignity and well-being of all individuals as the fundamental human rights principles. From this commitment, a positive obligation arises of states to provide asylum-seeking children with protection and humanitarian assistance, irrespective of the child's accompanying status. The thesis determines the extent of the violations of Article 3 of the ECHR in the detention conditions of migrant minors and identifies the contributing factors to these violations. The child's extreme vulnerability stands as the decisive factor, taking precedence over any considerations concerning the migration status of the child. When determining a violation of Article 3 of the ECHR, the ECtHR takes into consideration the children's young age, the duration of the detention and the suitability of the premises with regard to the specific needs of children.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Human rights law; European Convention on Human Rights; migrant minors; detention